Performa Kuat Tekan Mortar Geopolimer Berbasis Fly Ash dengan Variasi Rasio Alkali Aktivator: Performa Kuat Tekan Mortar Geopolimer Berbasis Fly Ash dengan Variasi - Sri Nur Akifa; Tikara, Medi; Adam, Andi Arham; Ramadhan, Bayu Rahmat; Wahidin, Suci Amalia Namira (Paulus Civil Engineering Journal, 2025)
The demand for environmentally friendly construction materials is increasing in line with efforts to reduce carbon emissions and utilize industrial waste. Portland cement contributes approximately 8% of global CO₂ emissions. Geopolymers, derived from aluminosilicate-based fly ash, have been developed as an alternative to conventional cement. The aim of this study is to evaluate the effect of varying alkali activator compositions on the compressive strength of fly ash-based geopolymer mortar type F. The fly ash was obtained from the Mpanau power plant and activated using a combination of Sodium Silicate (Na₂SiO₃) and Sodium Hydroxide (NaOH). The samples were prepared in the form of 50 × 50 × 50 mm cube mortars with a mass ratio of fly ash to sand of 1:2.75 and a water-to-solid ratio (w/s) of 0.35. The activator dosages applied were 25%, 40%, and 55% of the fly ash weight, with the ratio of Sodium Silicate to total activator (W/A) set at 0, 0.3, 0.5, 0.7, and 1. Compressive strength tests were conducted at curing ages of 3, 7, 14, and 28 days to assess the development of mechanical properties over time. The results indicated that increasing both the activator dosage and W/A ratio significantly affected the compressive strength characteristics of the mortar. The optimum compressive strength of 24.72 MPa was achieved with an activator dosage of 55% and a W/A ratio of 0.5 at 28 days. These findings suggest that geopolymer mortar with this composition has the potential to be applied as an environmentally friendly alternative structural material.